2019
DOI: 10.1088/1742-6596/1280/5/052039
|View full text |Cite
|
Sign up to set email alerts
|

The influence of scientific creativity and critical worksheets (SCCW) on creative thinking skills and critical scientific as well as students’ cognitive abilities on project-based learning work and energy concepts

Abstract: This study describes the influence of scientific creativity and critical worksheet (SCCW) to the creative thinking and scientific critical as well as students’ cognitive ability of Work and Energy concept. The aim of this study was to find out the improvement of cognitive ability, creative thinking skill and critically scientific students with applied model of project-based learning integrated with SCCW and conventional student worksheet (CSW). This study is based on one of the 21st Century Partnership Learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 9 publications
0
5
0
3
Order By: Relevance
“…(4) Adaptive Learning Pathways Future students should not only actively learn knowledge and master key skills. It is more important to be able to transform knowledge and skills into higher-order cognitive abilities, critical thinking, and innovative and creative talents in their social lives [85,86]. Therefore, providing adaptive learning pathways for students' competency development should be considered an important pathway to meet future challenges and enhance national educational strength and civic literacy.…”
Section: Foundations Of Intelligent Education Researchmentioning
confidence: 99%
“…(4) Adaptive Learning Pathways Future students should not only actively learn knowledge and master key skills. It is more important to be able to transform knowledge and skills into higher-order cognitive abilities, critical thinking, and innovative and creative talents in their social lives [85,86]. Therefore, providing adaptive learning pathways for students' competency development should be considered an important pathway to meet future challenges and enhance national educational strength and civic literacy.…”
Section: Foundations Of Intelligent Education Researchmentioning
confidence: 99%
“…Hasil penelitian menyimpulkan bahwa untuk meningkatkan kompetensi siswa pada pemograman PLC, pihak pendidik sebaiknya menerapkan model PBL berbantuan kit pelatihan untuk memudahkan pemahaman siswa namun belum berhasil meningkatkan kemampuan berpikir kritis siswa. [6] juga telah menyelesaikan penelitian untuk mengetahui peningkatan kemampuan kognitif dan kemampuan berpikir kritis siswa dengan model Project-Based Learning (PBL) yang terintegrasi dengan scientific creativity and critical worksheets (SCCW) dan Conventional student worksheet (CSW) pada siswa SMA. Penggunaan SCCW didapatkan lebih efektif daripada penggunaan CSW dalam meningkatkan kemampuan berpikir kritis serta kognitif siswa.…”
Section: Pendahuluanunclassified
“…Literature has shown that the contents of the recent studies related to scientific creativity are as follows: impact and relationships of different learning and teaching approaches and activities on scientific creativity (Akcanca & Cerrah Ozsevgec, 2017;Astutik, Susantini, Madlazim, Mohamad, & Supeno, 2020;Dewantara, Mahtari, Nur, Yuanita, & Sunarti, 2020;Karademir, 2016;Kozhevnikov, Kozhevnikov, Yu, & Blazhenkova 2013;Panjaitan & Siagian, 2020;Siew & Ambo, 2020;Wicaksono, 2020;Wulansari, Rusnayati, Saepuzaman, Karim, & Feranie, 2019;Zhao, Zhang, Heng, & Qi, 2021;Zhou, 2021), the effects of STEM and STEAM applications on scientific creativity (Calisici & Benzer, 2021;Genek & Doganca Kucuk, 2020;Rasul et al, 2018;Siew & Ambo, 2020), the effects of different thinking models on scientific creativity and the relationships between them (Demir, 2015;Forthmann, Szardenings, & Dumas, 2020;Vries & Lubart, 2017;Wulansari et al, 2019;Zhu, Shang, Jiang, Pei, & Su, 2019), perceptions, attitudes, and beliefs related to scientific creativity and the impact of scientific creativity on academic achievement (Calisici & Benzer, 2021;Demirhan & Sahin, 2021;Lee & Park, 2021;Ndeke, Okere, & Keraro, 2016), evaluation of the relationship between problem-solving skills, questioning skills, and scientific process skills, and scientific creativity (Chen, Hu, & Plicher 2016;Panjaitan & Siagian, 2020;Utemov et al, 2020;Yang et al, 2016;Dewantara et al, 2020), effects of science games and toys, animations, and WEB tutorials on scientific creativity (Atesgoz & Sak, 2021;Demir Kacan, 2015;…”
Section: Scientific Creativitymentioning
confidence: 99%